FRI0352 Juvenile dermatomyositis: Features and outcome according to age at onset. (23rd January 2014) - Katsicas, M.M.; Esquivel, P.; Russo, R.
Abstract : Background: Juvenile Dermatomyositis (JDM) is a multisystem autoimmune disease characterized by cutaneous and muscular inflammation. Disease onset is more frequent between age 4 and 10 years, with a peak at 6 years. There is little information about disease features in children with age at onset lower than 4 years.(1) Objectives: To identify disease features and outcome in a cohort of patients with JDM and to search for associations with age at onset. Methods: Patients with JDM were followed at the pediatric rheumatology clinic of a tertiary hospital since disease onset (defined as the first 6 months of the disease course), over the past 17 years. Only patients with disease duration >2 years were included. They were divided into groups according to age at disease onset: group A (0-4 years); group B (over 4 years).Variables at onset: age, sex, residence (distance in km between patient's residence and our center), disease duration at first visit, serum muscle enzymes (CK, aldolase, SGOT, SGPT, LDH), muscle strength (as measured by CMAS), presence of dysphagia, dysphonia, extra musculo-cutaneous features and hematological data. Variables during disease course: follow-up time, cumulative steroid dose, course of the disease (monophasic, polyphasic or chronic), use of immunosuppressors, presence of calcinosis and lipodystrophy, number of flares, functional capacity (as measured by CHAQ), damage (MDI). Statistical analysis included Chi 2 and Wilcoxon Rank sum test. Results: 114 patients were included (75F, 39M). Median follow up was 5.6 years. Group A: 17 patients (15%) sex ratio:1:1; Group B: 97 (85%) sex ratio 1:2. There were significant differences between groups A and B at onset: disease duration at first visit (median 5.5 vs 3 months p=0.009); serum aldolase level (median 4.66 vs 7.55; p=0.042). Extra-musculocutaneous features (parotidomegaly, cholestasis, seizures, hepatoespenomegaly, pneumonitis) were more frequent in group A (p=0.0025). There were no significant differences in time of follow-up, distance to our center, cumulative steroid dose, course of the disease, use of immunosuppressors, presence of calcinosis, neither number of flares (groupA: 37.5% vs group B: 29%). Lipodystrophy was more frequent in group A (35% vs 10%) p=0.014. Outcome measures showed differences in groups: CHAQ >0.5: 53% vs 19% (p=0.034); CMAS (medians): 47 vs 51 (p=0.0039); MDI (medians): 2 and 1 (p=0.02). Group A showed damage in muscular, cutaneous, skeletal, endocrine and ocular domains. Conclusions: There were significant differences according to age at onset. Patients with a younger age at onset show lipodystrophy more frequently and have uncommon features at onset. Poor prognosis in terms of disability and damage was observed in this group. These findings suggest the existence of a distinct subgroup of JDM. References: Pachman L et al. History of infection Before the Onset of Juvenile Dermatomyositis: Results From the National Institute of Arthritis and Musculoskeletal and Skin Diseases Research Registry. Arthitis Rheum 2005; 53:166-172. Disclosure of Interest: None Declared